SISTEM PENDUKUNG KEPUTUSAN REKOMENDASI PEMBELIAN LAPTOP MENGGUNAKAN METODE FUZZY DAN METODE SIMPLE ADDITIVE WEIGHTING - kurnialensya; Yuli Fitrianto (Elkom : Jurnal Elektronika dan Komputer, 2023)
In buying a laptop, you need to look at the specifications and standards that are tailored to your needs and requirements. Some of the standards and requirements include looking at several aspects of the criteria including the price of the laptop, RAM (random access memory), processor, hard drive capacity, screen size, VGA (video graphic adapter), battery power, weight, length of warranty, availability of spare parts, service range center. The fuzzy method is a method that makes it easy to find a value that is still vague and also linguistic, the use of the sample additive weighting (SAW) method is used to assist calculations in supporting decision making. The choice of using the SAW method is simpler in calculations, but the results of the calculations are accurate. From the results of calculations using the SAW method, it is calculated that between laptop 1 to laptop 7 with a price preference weight of 30, RAM 10, processor 10, hard disk capacity 10, screen size 5, VGA 3 (video graphic adapter), battery power 7, weight 5 , length of warranty 10, availability of spare parts 5, distance to service center 5, the highest order starts from laptop 1 with a total value of 18.4, laptop 7 with a value of 16.6, laptop 6 with a value of 13.6, laptop 5 with a value of 13.5, laptop 3 with a value of 13.2, laptop 4 with a value of 11.2, laptop 2 with a value of 8.9. The results of the assessment can change according to the needs of laptop buyers, who are more concerned with which criterion has the most important weight.